45. OUTPATIENTS’ SATISFACTION AND SOME RELATED FACTORS AT INOMAS TRADITIONAL MEDICINE CLINIC, HOANG MAI, HANOI IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe patient satisfaction using services at INOMAS Traditional Medicine Clinic and some related factors in 2024.Method: Analytical cross-sectional descriptive study.Results: The overall satisfaction rate of research subjects with the medical services used was relatively high (85.3%), the remaining 14.7% were not satisfied with the service. In particular, the satisfaction rate for 7 aspects “administrative procedures”, “daily treatment operations”, “information”, “patient service facilities”, “technicians' attitudes, medical staff”, “care outcomes” and “medical services at the clinic” are 91%, 88.1%, 91%, 95.3%, 96.4%, 83.1% and 89.6%. Analysis results show that gender is related to satisfaction with medical services with p = 0.003 (OR = 2.87, 95%CI = 1.41-5.82).Conclusion: The overall satisfaction rate of research subjects on the use of health service was 85.3%. Factors related to overall health service satisfaction with statistical significance p < 0.05 were only gender. Other factors such as income, professional education level, number of days and form of treatment no relationship with satisfaction with health services was found (with p > 0.05).
Keywords: Patient satisfaction; health service; INOMAS traditional medicine